2021
DOI: 10.3389/fonc.2021.642902
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Clinicopathological Value of Human Leukocyte Antigen G in Gastrointestinal Cancers: A Meta-Analysis

Abstract: BackgroundThe prognostic value of human leukocyte antigen G (HLA-G) expression in gastrointestinal (GI) cancers remains controversial. Thus, this meta-analysis aimed to summarize available evidence from case-control or cohort studies that evaluated this association.MethodsThe PubMed, EMBASE, Cochrane Library, and Web of Science databases were searched to identify relevant studies written in English published up to April 1, 2021, and with no initial date. Furthermore, the Google Scholar and Google databases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…Numerous studies have demonstrated that high HLA-G expression was associated with poor prognosis in gastrointestinal cancer patients ( 28 32 ). However, there are few studies showing that there is no significant relationship between HLA-G expression and the prognosis of gastrointestinal cancers ( 33 – 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that high HLA-G expression was associated with poor prognosis in gastrointestinal cancer patients ( 28 32 ). However, there are few studies showing that there is no significant relationship between HLA-G expression and the prognosis of gastrointestinal cancers ( 33 – 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the conclusion drawn from previous studies that tumour HLA-G expression is closely related to tumour progression and poor clinical outcomes in patients with cancer. A recent meta-analysis by Peng et al, performed on immunohistochemical and ELISA dosage [50], showed significant association of HLA-G with poor prognosis in gastric cancer. In addition, this meta-analysis showed that there was a significant correlation between HLA-G expression and TNM stage, lymph node status, and histological grade [50].…”
Section: Discussionmentioning
confidence: 99%
“…The non-classical MHC class I molecule HLA-G is under non-malignant conditions mainly expressed on extravillious trophoblasts [327,328], which invade maternal tissues during pregnancy, and promotes immune tolerance at the fetal-maternal interface [329][330][331]. Interestingly, many tumors, including colorectal, renal, breast, and lung tumors, have been shown to express HLA-G, which has often been associated with a worse outcome [201,[332][333][334][335][336]. In cancer, HLA-G expression can be involved in the evasion from anti-tumor immunity [337].…”
Section: Non-classical Hla Class I Molecules In Tumorsmentioning
confidence: 99%